Human factors perspective adoption of cloud-based application in higher education among student in UTM - Gohari, Marjan Moshfegh (2013)
Adoption of cloud based applications as a new trend in the field of IT and technology, and identification of key factors influencing this adoption process is of high importance. Currently, dedicated studies on the phase of adoption process in educational domains based on the cloud based applications was not paid attention, and works in this domain are very limited. Moreover, despite of several frameworks offered in the technological aspects and security issues, no suitable framework is offered. In this study, role of human factors as one of the factors influences the adoption process of cloud based applications among students of Universiti Teknologi Malaysia has been examined. The research aims to identify the human factors influencing the cloud based applications adoption in higher education setting, and evaluate the level of impact for each candidate factor on the dependent factor variable. Random sampling and questionnaire method were used to examine the propositions of the study. For a valid methodological background, a modified version of the common Technology Acceptance was used. Factor analysis and Validation tests of sample data; regression and ANOVA analysis were performed to evaluate and model the relationship of the impacts, respectively. The outcome of analysis indicates that the acceptance of cloud based applications in a higher education section such as UTM can be explained and predicted by different human factors and predictors. The data collection method of this study was questionnaire and the findings of this study indicates that some human factors such as Exposure, Motivation and Self-Efficacy can have high impact to this adoption process significantly. The results also revealed useful information for address this issue and eventually a model fit for the adoption of cloud based applications based on human factors in higher education was offered